Resources as part of the narrative in biography. A study of the extent to which letters contribute to the narrative in biography, with reference to JC Kannemeyer’s biography Leroux : ’n Lewe and Charles Bukowski by Barry Miles - Pieterse, Henning Jonathan, 1960- (University of Pretoria, 2017)
Thesis (PhD)--University of Pretoria, 2016.